On the global geodynamic consequences of different phase boundary morphologies - G. T. Morgan; J. H. Davies; R. Myhill; J. Panton (Solid Earth)
Phase transitions can influence mantle convection patterns, inhibiting or promoting vertical flow. One such transition is the ringwoodite-to-bridgmanite plus periclase transition, which has a negative Clapeyron slope and therefore reduces mantle flow between the upper and lower mantle. Interactions between different transitions and significant Clapeyron slope curvature can potentially result in complexities in mid-mantle geodynamics – affecting the stagnation of slabs and free upward motion of plumes.